Blok D, Kompleks Islam Putrajaya - Arshad, Ieman; Zulkfilee, Muhammad Taufiq; Mustafa Kamal, Nur Faqihah Wathiqah; Kamarudin, Nur Syazwana (2024)
Kompleks Islam Putrajaya (KIP), which is situated in Putrajaya's Precinct 3, was constructed across a 2.21-hectare plot, and finished in August 2016. The four building blocks that make up the KIP are furnished with a variety of amenities. Built on the foundation of stunning modern urban architecture that harmonises traditional Islamic architecture with contemporary style. The goal of the KIP building concept was to create a more spacious and pleasant workplace. In every key region, there are also accessible facilities for the disabled.